Traumatic shock – the problem of contemporary medicine and public health - Dąbrowski, Andrzej; Lichota, Elżbieta; Skrzypek, Agata; Wojtaszek, Marek; Maciejewski, Ryszard; Głowacka, Magdalena (Polish Journal of Public Health, 2009)
The pandemic of traumas was long ago considered the most expensive and the most severe war of contemporary world. The effects of traumatism, such as death or prolonged disability, besides personal loses and high costs of treatment, are great burden to a society.Diagnostic-therapeutic procedure in multiorgan injuries located in many places is a complex problem and requires appropriate organizational activities. In spite of greater progress in traumatology and establishing of procedural standards for pre-hospitalisation period and hospitalisation, the death rate is still high and reaches 15-30%.The leading and primary cause of deaths of the injury victims during the fi rst minutes in pre-hospitalisation period and during consecutive several hours at the hospital is the haemorrhage. The traumatic shock is of hypovolemic type in the course of massive haemorrhages. Cardogenic, neurogenic or obturative cause is much more rare [1].The principal role in treatment of haemorrhagic shock is controlling of the source of haemorrhage and supplementing of volemia.The prognosis in haemorrhagic shock is signifi cantly improved by an instant and adequate implementation of liquid therapy and the response of the organism to vascular bed fi lling. The patients subjected to liquid therapy during pre-hospitalisation period according with ATLS were surviving 4 times more than patients who were not treated with liquid therapy.